Influência do teor de hidrofugação na absorção de paredes de gesso - Almaí Santos (2017)
Currently, gypsum blocks are designed for interior walls of residential and commercial buildings, in reinforced concrete structures or similar. In the Brazilian Northeast, the construction industry has also applied masonry of gypsum blocks on façades, despite the lack of normative and regulatory framework. Most of the building materials have open porosity, such as mortars, which absorb water by capillarity and allow the water to migrate under liquid or vapor form through its voids. The objective of this work is to evaluate the capillary absorption of gypsum walls with different levels of water repellency and to show their influence by evaluating the different materials that make up the wall: plaster block, plaster coating and glue plaster. For the accomplishment of the tests the procedure defined by the European standard EN ISO 15148-2002. Was applied. The analysis was based on gypsum test pieces for non-water-repellent, standard blocks of the hydro type, with the following water repellency percentages: 0.08%, 0.1%, 0.15%, 0.2% 25%, 0.3%, 0.4% and 0.5%. The same analysis was also applied to gypsum coating samples (water content of 0.3%, 0.5% and 0.7%) and gypsum glue (water repellency content between 0.2% and 0.5%). The results obtained evidenced a logarithmic relationship between the water repellent content and the capillary absorption coefficient of the different gypsum products.